Selective hydrothermal reductions using geomimicry. Issue 15 (17th July 2019) - Bockisch, Christiana; Lorance, Edward D.; Shaver, Garrett; Williams, Lynda B.; Hartnett, Hilairy E.; Shock, Everett L.; Gould, Ian R.
Abstract : Reduction of carbon–carbon π-bonds has been demonstrated using iron powder as the reductant and simple powdered nickel as the catalyst in water as the solvent at 250 °C and the saturated water vapor pressure, 40 bars. Abstract : Reduction of carbon–carbon π-bonds has been demonstrated using iron powder as the reductant and simple powdered nickel as the catalyst in water as the solvent at 250 °C and the saturated water vapor pressure, 40 bars. Stereochemical, kinetic and electronic probes of the mechanism suggest reaction via a conventional Horiuti–Polyani process for hydrogenation at the nickel metal surface. Selective reduction of carbon–carbon π-bonds is observed in the presence of other functional groups. The reactions use benign and Earth-abundant reagents that are at low depletion risk and take place in water as the only solvent under conditions that are characteristic of many geochemical processes.